Mapping research trends on STEM-integrated project-based learning in physics education: a bibliometric review - Syaifuddin, Syaifuddin; Sarwi, Sarwi; Hartono, Hartono; Nuswowati, Murbangun (Intelektual Pustaka Media Utama, 2025)
This study presents a bibliometric review analysis of science, technology, engineering, and mathematics (STEM) integrated project-based learning (PjBL) used in promoting meaningful physics learning at the secondary education level. It aims to provide in-depth information about the research landscape of STEM-integrated PjBL models in physics learning outcomes in senior high schools and its contribution to implementing the Merdeka Curriculum in Indonesia. For this purpose, 72 articles published between 2013 and 2023 from the Scopus database were selected based on predetermined criteria. The selected articles were analyzed regarding publication trends, key research themes, citation analysis, and keywords. The findings of this study highlight a network of actively participating authors, institutions, and research groups in this field. In addition, this comprehensive review offers an understanding of the current state and opportunities in this research field and identifies further exploration areas and gap analysis. The implication of the results of this literature review is to critically know the existence of a gap analysis so that one of the next studies is to be able to develop a STEM integrated PjBL model with a contextual, cultural and multidisciplinary approach to promote sustainable development.